Electron microscopy and tomography reveal that sodium 2‐naphthalene sulfonate incorporated into perming solutions swells and tilts trichocyte intermediate filaments causing straightening of curly Japanese human hair. (17th April 2019) - Bryson, W. G.; Harland, D. P.; Caldwell, J. P.; Vernon, J. A.; Walls, R. J.; Woods, J. L.; Nagase, S.; Itou, T.; Koike, K.
Abstract: Objective: A new hair‐care process has been specifically developed for the straightening of curved Japanese woman's hair1 . The process included sodium 2‐naphthalene sulfonate (SNS) in the reduction and oxidation steps of a conventional perming process. Our objective was to develop an understanding of how this process caused hair straightening by measuring the changes to morphology and ultrastructure between untreated, conventionally permed and SNS permed hair. Untreated and SNS permed Merino wool fibres were used to confirm structural changes. Methods: Japanese hair samples were measured for single‐fibre curvature before and after perming treatments. A silver staining method was developed to stain hair fibres without changing fibre curvature so that transmission electron microscopy could be used to measure changes in the lateral dimensions of all structural components from the cellular to protein filament level. Electron tomography determined intermediate filament slopes and slope changes after SNS perming relative to the central longitudinal axis of the fibre. Results: SNS perming was found to cause greater lateral swelling than conventional perming of: the paracortical cells of wool; the cuticle, the cuticular cell membrane complex and the macrofibrillar centre‐to‐centre distance of hair; and of the intermediate filaments in wool and hair. In curved hair, SNS perming caused the intermediate filaments of the helical macrofibrils to simultaneously swell and to tilt further, resulting in the slight longitudinal contraction of the macrofibrils. The overall swelling and tilting was greatest in the helical macrofibrils of Type B cortical cells predominately located in the convex fibre half. The presence of a higher percentage of helical macrofibrils in the convex fibre half than in the concave fibre half caused a contraction differential between the two halves leading to straighten of the curved fibre. A mechanical model was proposed to explain how SNS perming straightened curly hair. Conclusion: The effects of conventional and SNS perming on the morphological and ultrastructural components of curved Japanese hair and high‐curl Merino wool fibres have given clear insights into understanding the mechanism of fibre curvature change. Abstract : Mechanism of straightening naturally curly hair by sodium 2‐naphthalene sulfonate perming. Type C cells predominant in the concave fibre half contain a mixture of macrofibrils, some with helical but most with non‐helical intermediate filament arrangements which on average will swell equally but contract less than Type B cell macrofibrils with helical intermediate filament arrangements predominant in the convex fibre half. The overall result is that greater longitudinal contraction of the cortex in the convex fibre half will cause the fibre to straighten.